20th Biennial BDS Conference 2018 – Tour 2: Dwr Cymru Welsh Water Reservoirs – Shon Sheffrey and Rhymney Bridge No. 2. Issue 1 (29th March 2019) - Grierson, Richard
Abstract : This paper is an account of the 20th Biennial British Dam Society (BDS) Conference 2018 – Site Tour 2: Dwr Cymru Welsh Water Reservoirs – Shon Sheffrey and Rhymney Bridge No. 2. It describes the general background of the visits including recent upgrade works to the spillways at both sites. At Shon Sheffrey works were complete to upgrade the spillway following recommendations made in the interests of safety in 2010 to investigate and upgrade the spillway of the reservoir as well as grouting to stem leakage through the embankment. At Rhymney Bridge No. 2 works were complete following an incident in 2013 where the spillway failed due to uplift pressures during a major storm event. Approximately 40 BDS delegates visited both Shon Sheffrey and Rhymney Bridge No. 2 reservoirs owned and managed by Dwr Cymru Welsh Water.